Is Posner right? An empirical test of the Posner argument for transferring health spending from old women to old men - Christoph Wunder; Johannes Schwarze (Verein für Socialpolitik, 2010)
Posner (1995) proposes the redistribution of health spending from old women to old men to equalize life expectancy. His argument is based on the assumption that women's utility is higher if they are married. Using life satisfaction data from the German Socio-Economic Panel Study (SOEP), we conduct an empirical test of this assumption. We apply a two-step estimation strategy: first, we use a propensity score matching approach to generate a control group of nonwidowed women. The average level of life satisfaction in the control group serves as a reference to measure the degree of adaptation to widowhood. In the second step, the life satisfaction trajectories of both groups are estimated using penalized spline regressions. The results suggest bereavement has no enduring effect on life satisfaction, and that is evidence against Posner's assumption.
Keywords: C14; D10; I31; 330; widowhood; adaptation; subjective well-being; life satisfaction; penalized spline regression; propensity score matching